We have to solve the equations:

x + y = -3 ...(1)

x + z = -2 ...(2)

xy + yz + xz = 2 ...(3)

From (1)

x + y = -3

=> y = -3 - x

From (2)

x + z = -2

=> z = -2...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve the equations:

x + y = -3 ...(1)

x + z = -2 ...(2)

xy + yz + xz = 2 ...(3)

From (1)

x + y = -3

=> y = -3 - x

From (2)

x + z = -2

=> z = -2 - x

Substitute these in (3)

xy + yz + xz = 2

=> x(-3 - x) + (-3 - x)(-2 - x) + x(-2 - x) = 2

=> -3x- x^2 + 6 + 3x + 2x + x^2 - 2x - x^2 = 2

=> - x^2 + 6 = 2

=> x^2 = 4

=> x = 2 and x = -2

y = -3 - x = -5 and -1

z = -2 - x = -4 and 0

**The values of x, y and z are (2, -5, -4) and (-2, -1, 0).**